Application of fundamental solutions to the static analysis of thin plates subjected to transverse and in-plane loading = Zastosowanie funkcji fundamentalnych w analizie statycznej płyt cienkich obciążonych poprzecznie i w płaszczyźnie - Pawlak, Zdzisław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this paper static analysis of Kirchhoff plates is considered. A transverse and in-plane loading is taken into consideration. The Finite Strip Method is used and the suitable fundamental solutions are applied. According to the finite strip method a continuous structure is divided into a set of identical elements simply supported on opposite edges. The unknowns are deflections and transverse slope variables along the nodal lines.
Keywords: metoda pasm skończonych; płyty Kirchhoffa; analiza statyczna; płyty cienkie; finite strip method; Kirchhoff plates; static analysis; thin plates